2008
DOI: 10.1103/physreve.77.041905
|View full text |Cite
|
Sign up to set email alerts
|

Contact-mediated cell-assisted cell proliferation in a model eukaryotic single-cell organism: An explanation for the lag phase in shaken cell culture

Abstract: In cell culture, when cells are inoculated into fresh media, there can be a period of slow (or lag phase) growth followed by a transition to exponential growth. This period of slow growth is usually attributed to the cells' adaptation to a new environment. However, we argue that, based on observations of shaken suspension culture of Dictyostelium discoideum, a model single-cell eukaryote, this transition is due to a density effect. Attempts to demonstrate the existence of implicit cell signaling via long-range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 15 publications
3
18
2
Order By: Relevance
“…The cells grown in suspensions have a broader size distribution ( Fig. 2a) than those on substrates, consistent with previous observations of cell clusters [18] and multinuclear cells [17], since the lack of solid substrate probably impedes cytokinesis. These are all counted as a single particle by automated counting (Fig.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The cells grown in suspensions have a broader size distribution ( Fig. 2a) than those on substrates, consistent with previous observations of cell clusters [18] and multinuclear cells [17], since the lack of solid substrate probably impedes cytokinesis. These are all counted as a single particle by automated counting (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Next, we investigate the possibility that cells secrete a growth factor or a mitogen that serves as a synchronization signal. We analyzed the microfluidic experiments we performed previously [18] with cells grown on a substrate in a PDMS microfluidic device (Fig. 2c).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…‫ء‬ indicates a P value of Ͻ0.05, ‫ءء‬ indicates a P value of Ͻ0.01, and ‫ءءء‬ indicates a P value of Ͻ0.001 (t test). (34), and at higher densities, high levels of accumulated endogenous AprA and CfaD can interfere with the assay. We measured the effect of rAprA and rCfaD at 18 h, as we have observed that culturing of cells with exogenous recombinant proteins past 24 h leads to degradation and/or ingestion of the recombinant proteins (our unpublished data).…”
Section: Figmentioning
confidence: 99%